Multicomponent Reactions (MCRs) with o‐Quinone Methides. Issue 3 (2nd February 2022) - Martins, Maria Tereza M.; Dias, Flaviana Rodrigues F.; de Moraes, Raphael Silva M.; da Silva, Marcos Felipe V.; Lucio, Kaio R.; D'Oliveira Góes, Karina; do Nascimento, Patrick A.; da Silva, André S. S.; Ferreira, Vitor F.; Cunha, Anna C.
Abstract: This article presents a comprehensive overview of multicomponent reactions (MCRs) that proceed via ortho ‐quinone methide intermediates ( o ‐QM) generated in the reaction medium. Examples of applications involving these highly reactive intermediates in organic synthesis and biological processes (e. g., biosynthetic pathways, prodrug cleavage and electrophilic capture of biological nucleophiles) are also described. QMs are often generated by eliminative processes of phenol derivatives or by photochemical reactions, including reversible generation in photochromic substances. This class of compounds can undergo various reaction types, including nucleophilic attack at the methide carbon, with subsequent rearomatization, and react with electron‐rich dienophiles in inverse‐electron demand hetero‐Diels‐Alder reactions. Its versatile reactivity has been explored in the context of cascade reactions for the construction of several classes of substances, including complex natural products. Abstract : This article presents a comprehensive overview of multicomponent reactions (MCRs) that proceed via ortho ‐quinone methide intermediates ( o ‐QM) generated in the reaction medium. Examples of applications involving these highly reactive intermediates in organic synthesis and biological processes (e. g., biosynthetic pathways, prodrug cleavage and electrophilic capture of biological nucleophiles) are also described.